Lotus tenuis in Association with Arbuscular Mycorrhizal Fungi Is More Tolerant to Partial Submergence than to High-Intensity Defoliation - Ileana García (International Journal of Plant Biology, 2025)
This study aimed to investigate the effect of the association of Lotus tenuis with arbuscular mycorrhizal fungi (AMF) on its development under high defoliation intensity or partial submergence in a P-deficient soil of the Salado River Basin in a pot experiment. L. tenuis mycorrhizal plants showed higher tolerance to partial submergence (91%) than to high defoliation intensity (57%). Shoot biomass was the highest in mycorrhizal non-stressed and submerged plants (11.71 g and 12.06 g, respectively), and decreased by 38% in defoliated plants. Both stress conditions caused a negative effect on root growth of plants with or without AMF. High-intensity defoliation can be considered the most stressful scenario for mycorrhizal L. tenuis plants and AMF play a more marked role in P nutrition. Under submergence, AMF caused a net effect on L. tenuis growth, improving carbon and P resource distribution to sustain shoot growth and elongation. Root AMF colonization and nodulation decreased under submergence. High arbuscular colonization percentages were reached under both stress conditions, indicating that the symbiosis may be functional. L. tenuis roots can act as a reservoir of the fungal community under severe stress conditions, allowing the preservation of the AMF inoculum.